Faster, better, cheaper : low-cost innovation in the U.S. space program - McCurdy, Howard E. (New series in NASA history., 2001)
While the technological innovation and space exploration approach that McCurdy describes is still controversial, the historical perspective on its disappointments and triumphs points to ways of developing ""faster, better, and cheaperas a management manifesto.